2021
DOI: 10.4329/wjr.v13.i6.171
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 imaging: Diagnostic approaches, challenges, and evolving advances

Abstract: The role of radiology and the radiologist have evolved throughout the coronavirus disease-2019 (COVID-19) pandemic. Early on, chest computed tomography was used for screening and diagnosis of COVID-19; however, it is now indicated for high-risk patients, those with severe disease, or in areas where polymerase chain reaction testing is sparsely available. Chest radiography is now utilized mainly for monitoring disease progression in hospitalized patients showing signs of worsening clinical status. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 145 publications
1
6
0
3
Order By: Relevance
“…We fully agree with these studies [ 46 , 47 , 48 , 49 , 50 ]. We believe that challenges and acceptance of the integration of technology must be interconnected and go hand in hand so that expectations are not disillusioned, and we can obtain Artificial Intelligence that offers us an increasingly effective and health-oriented useful approach.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We fully agree with these studies [ 46 , 47 , 48 , 49 , 50 ]. We believe that challenges and acceptance of the integration of technology must be interconnected and go hand in hand so that expectations are not disillusioned, and we can obtain Artificial Intelligence that offers us an increasingly effective and health-oriented useful approach.…”
Section: Discussionsupporting
confidence: 92%
“…A Sentiment analysis review conducted on Twitter showed an increasing attention on the integration of Artificial Intelligence in Digital Radiology [ 46 ]. Other review studies clearly showed that the pandemic represented an important engine for the development of this field [ 47 , 48 , 49 ] and an important lesson on how to continue for the future, as highlighted in the perspective reported in [ 37 ]. Other studies considered Artificial Intelligence in Digital Radiology in terms of impact to equity [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A deep analysis conducted on social media highlighted a growing attention on the integration of AI in DR within the health domain [ 32 ]. Surely, the COVID-19 pandemic that people are experiencing has also represented an important push in this direction [ 37 , 38 , 39 ] and given an important lesson for the future [ 40 ]. An improvement in equity of care is also expected from the integration of AI in DR into the health domain [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Подобные отклонения могут быть связаны как с региональными различиями в типе протекания инфекции, так и с особенностями интерпретации вопросов интервьюера в телефонном опросе. Данные КТ ОГК стали важным диагностическим критерием для выявления и оценки тяжести течения COVID-19 за время эпидемии вируса SARS-CoV-2 [18]. В нашем исследовании тяжесть поражения легких по КТ значительно коррелировала с большим количеством параметров, что в дальнейшем, возможно, позволит использовать их для предварительной оценки тяжести поражения легких, своевременной госпитализации пациентов и предотвращения летальных исходов.…”
Section: Discussionunclassified